Testing SAP R/3 : a manager's step-by-step guide - Fajardo, Jose, 1974- (J. Wiley & Sons, 2007)
"A must read for project managers, test managers, and configuration leads who want to establish a testing framework from the ground up based on industry-established principles. Testing SAP R/3 contains contributions from industry leaders in the fields of SAP testing, test tool automation, and templates to help project managers and test managers establish immediate testing best practices. Its step-by-step discussion covers all aspects of SAP testing from preparation to resolution of defects in order to acheive an efficiently managed SAP system."--Jacket